Βελτίωση της ποιότητας στην τριτοβάθμια εκπαίδευση: διερεύνηση των αντιλήψεων των φοιτητών για τα κριτήρια αξιολόγησης του αποτελεσματικού καθηγητή πανεπιστημίου - Παππά Μαρία; Θανόπουλος Γιάννης Ν. (SPOUDAI Journal of Economics and Business, 2006)
The evaluation and continuous improvement of the quality of teaching and learning within a university setting has been always a major concern of the accreditation agencies. The purpose of this study is to examine the importance of the criteria of the effective university professor based on student-originating variables (gender, student status). In order to achieve our purpose student's perceptions of the «ideal teacher» were studied and an appropriate instrument was constructed measuring the importance of 42 criteria of teaching effectiveness. The data were collected from a sample of 289 management undergraduate and postgraduate students, who were asked to rate criteria of teacher effectiveness based on the student's rating (importance) in academic education. In many instances different criteria are supported by undergraduate versus postgraduate students and by male versus female students.